CLIMATIC DATA COMPARISON BETWEEN MID-LATITUDE AZORES (NORTH ATLANTIC) AND TRISTAN DA CUNHA (SOUTH ATLANTIC) ISLANDS - RUSU, Raularian (Studia Universitatis Babeș-Bolyai Geographia, 2023)
The Azores islands in the North Atlantic and the Tristan da Cunha islands in the South Atlantic are approximately located at the same latitude, stretching between 36 and 41 degrees North and South respectively. Nevertheless, there are important climatic differences between the two archipelagos. The average annual temperature is higher in the Azores by more than 3 degrees, while the amount of precipitation is higher in Tristan da Cunha by about 600 mm/year on average. The warmer climate of the Azores may be explained by several contributing factors, such as: the smaller distance to the nearest continental landmass – less than 1500 km, compared to more than 2700 km in the case of Tristan da Cunha; the land mass of the islands themselves, as the Azores are much larger; the location of the Azores in the area of the North Atlantic High, with more stable weather and a higher amount of sunshine hours compared to the Tristan da Cunha islands, where westerlies prevail; and, not in the least, the influence of the Gulf Stream in the case of the Azores. The larger amount of precipitation in the case of Tristan da Cunha islands is due to their location on the southern flank of the South Atlantic High, which causes a higher degree of cloudiness and therefore more precipitation. The altitude is also a factor, as both archipelagos feature volcanic mountains rising above 2000 metres, providing a barrier for the air masses and determining orographic precipitation, especially on the windward side of the islands. The climate has had an impact on the settlement and human life on the islands. The Azores were settled immediately after their discovery in the 15th century and there is a rich social and economic life ever since. By contrast, the small community on Tristan da Cunha main island was formed only in the 19th century and has endured many hardships.